IMPORT SUBSTITUTION OF COMBINATION WIRE ROPE .PART .I. DESIGN ,PRODUCTION AND EVALUATION OF A PROTOTYPE COMBINATION WIRE ROPE - MEENAKUMARI, B; PANICKER, P A (Fishery Technology, 2017)
Model combination wire ropes with different covering materials were prepared and worked out specification for the prototype. A table modd hand operated wire rope twisting machine was also developed for this. Prototype combination wire rope was twisted in collaboration with M/s. South India Wire Ropes Ltd., Alwaye. Specification details, properties and field performance of the prototype studied are reported.